Kemiskinan di Ibukota Kalimantan Timur - Zuriatin Mawa; Eny Rochaida; Muliati Muliati (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
The purpose of this study is to discribe the lives of  illegal parking  attendants in Samarinda city.  The research method using qualitative research. Informants in this study is Mr. Fitriadi located in theTepian Mahakam. Mr. Edo is located in Pasar Pagi and Mr. Iwan located in Pasar Kedondong.  The result of this study indicate illegal parking attendant interpreter still relatively affluent families if measured from the level of revenue generated and compared to a standart poverty line in Samarinda city, but poor vulnarable in the event of price increases on basic necessities. They assume the illegal parking attendants profesion is a choice and compulsion. Furthermore, the existence of illegal parking attendants who become informant in this study received the help or support of mass organizations existing in Samarinda.Keywords: Illegal Parking Attendant